Moslem Sculptor (Negotiation of Sculptor at Prumpung Magelang Towards The Doctrine of Sculpting’s Prohibition on Islam) - Muh Zuhri; Ahmad Rafiq; Ahmad Mustofa (International Journal Ihya' 'Ulum al-Din, 2021)
Normatively, Islamic doctrine prohibits figurative art in the form of sculpture or painting. The prohibition actually comes not from the Koran but from various narrations of the Prophet's hadith. However, it has been transformed into an orthodox doctrine for its adherents. This research does not aim to find the essential meaning of the hadith text which prohibits figurative art, but to find out how the Moslem sculptors, who live at Prumpung Magelang area, respond and negotiate toward it, so in the end they decided to compromise with their profession as a sculptor. Reception theory is used in this study to map the creative reasoning model of Moslem sculptors when negotiating with texts. Through the reception approach, and field data collection through in-depth interviews with several informants consisting of Muslim sculptors at Prumpung Magelang, this research concludes that the existence of the statue, according to the perspective of the Moslem sculptors at Prumpung Magelang is merely works of art so that in existence there are no theological problems.